Developing and Validating the Scale of Economic Self-Efficacy. (August 2020) - Hoge, Gretchen L.; Stylianou, Amanda M.; Hetling, Andrea; Postmus, Judy L.
Experiencing intimate partner violence (IPV) and financial hardship are often intertwined. The dynamics of an abusive relationship may include economic abuse tactics that compromise a survivor's ability to work, pursue education, have access to financial resources, and establish financial skills, knowledge, and security. An increasingly common goal among programs serving IPV survivors is increasing financial empowerment through financial literacy. However, providing financial education alone may not be enough to improve financial behaviors. Psychological factors also play a role when individuals make financial choices. Economic self-efficacy focuses on the individual's perceived ability to perform economic or financial tasks, and may be considered a primary influence on one's ability to improve financial decisions and behaviors. The current study tests the reliability and validity of a Scale of Economic Self-Efficacy with a sample of female survivors of IPV. This study uses a calibration and validation analysis model including full and split-sample exploratory and confirmatory factor analyses, assesses for internal consistency, and examines correlation coefficients between economic self-efficacy, economic self-sufficiency, financial strain, and difficulty living with income. Findings indicate that the 10-item, unidimensional Scale of Economic Self-Efficacy demonstrates strong reliability and validity among this sample of IPV survivors. An ability to understand economic self-efficacy could facilitate individualized service approaches and allow practitioners to better support IPV survivors on their journey toward financial empowerment. Given the increase in programs focused on assets, financial empowerment, and economic well-being, the Scale of Economic Self-Efficacy has potential as a very timely and relevant tool in the design, implementation, and evaluation of such programs, and specifically for programs created for IPV survivors.